2015
DOI: 10.1080/10438599.2015.1109780
|View full text |Cite
|
Sign up to set email alerts
|

Managing portfolio risk in strategic technology management: evidence from a panel data-set of the world's largest R&D performers

Abstract: In this article we analyze the impact of firms' technology bases on their financial performance. By taking a strategic perspective of technology, we argue that it is not sufficient to analyze only the size or novelty/quality of the technology base as technology bases can best be understood as portfolios of individual technologies. In such a framework, risk consideration should be taken into account. More specifically, we argue that increasing technological breadth can serve as a hedge against the inherent unce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Suggesting that a broader range of R&D projects expands the knowledge base of a firm and improves the likelihood of success in new product introduction, Klingebiel and Rammer (2014) empirically show that the number of new product development projects is positively associated with the revenue generated from new products. Also, Neuhäusler et al (2016) use patent data with panel data analysis to show that broadening an investment portfolio increases the hedge against uncertainties, resulting in better financial performance. Furthermore, we suggest that managing various environmental concerns is similar to maintaining an investment portfolio.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Suggesting that a broader range of R&D projects expands the knowledge base of a firm and improves the likelihood of success in new product introduction, Klingebiel and Rammer (2014) empirically show that the number of new product development projects is positively associated with the revenue generated from new products. Also, Neuhäusler et al (2016) use patent data with panel data analysis to show that broadening an investment portfolio increases the hedge against uncertainties, resulting in better financial performance. Furthermore, we suggest that managing various environmental concerns is similar to maintaining an investment portfolio.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…With a limited understanding of managing multiple environmental concerns simultaneously in the literature, we leverage the similarities between environmental expenditures and R&D investment and refer to the portfolio management argument. A literature stream has examined portfolio management in product development and empirically shown that a broader portfolio expands firms' knowledge base and helps them hedge risks (Klingebiel & Rammer, 2014; Neuhäusler, Schubert, Frietsch, & Blind, 2016). Focusing on the difference between a firm's resource‐related environmental efficiency and its climate‐related environmental efficiency, we suggest that a firm with less difference reflects its managers' broader and balanced interests in addressing environmental concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Following these analyses, numerous studies have examined the impact of patent portfolios and their quality on firm value (e.g. after the seminal contribution by Griliches, 1981;Hall et al, 2005;Patacconi., 2013, andNeuhäusler et al, 2016). The majority of these studies have revealed a positive effect.…”
Section: Patentingmentioning
confidence: 99%
“…A long tradition of studies considers the impact of patenting on innovations and commercial success. Seminal contributions by Griliches (1981); Mansfield (1986), and Cohen et al (2000) focused on firms' involvement in patenting and studies about the influence of patent portfolios on firm market valuation, such as Belenzon and Patacconi (2013); Hall et al (2005), and Neuhäusler et al (2016), followed them.…”
Section: Introductionmentioning
confidence: 99%
“…High speed of technological change increases the importance of both asset augmentation and exploitation. Firms in fast changing, though not necessarily uncertain, technological environments have to be prepared for change and have to proactively adjust and develop their technology portfolio (Neuhäusler et al 2015). Augmenting their knowledge assets through internationalization is therefore critical, since rapid product cycles imply short periods for realizing returns from innovation (Klepper 1996).…”
Section: Discussionmentioning
confidence: 99%